Association between problematic social media use and psychological distress among college students: a cross-sectional study in China exploring the mediating role of eating disorders - Niaona Hu; Xiafang Xiao; Kim Lam Soh (BMJ Open)
Objectives This study aimed to examine the mediating role of eating disorders in the association between problematic social media use (PSMU) and psychological distress, including anxiety, depression and stress, among Chinese college students. The primary hypothesis was that eating disorders would partially mediate the relationship between PSMU and psychological distress.Design A cross-sectional study.Setting Participants were recruited from a vocational college in Jiangxi, China.Participants A total of 454 college students aged 18 years or older participated in the study. The median age was 19 years (IQR=18, 20), and 73.4% were male. Participants were included if they were enrolled in college and able to provide informed consent. Students undergoing psychological treatment or taking psychiatric medications were excluded.Primary outcome measures PSMU was assessed using the Bergen Social Media Addiction Scale, psychological distress was assessed using the Depression Anxiety Stress Scales-21 and eating disorder symptoms were assessed using the SCOFF questionnaire.Results PSMU was significantly associated with higher levels of psychological distress (r=0.321, p<0.05) and eating disorders (r=0.298, p<0.05). The mediation analysis showed that eating disorders accounted for 39.8% of the total effect of PSMU on psychological distress. The indirect effect of PSMU on psychological distress through eating disorders was statistically significant (B=0.119, SE=0.018, p<0.001).Conclusions Eating disorders play a partial mediating role in the relationship between PSMU and psychological distress among Chinese college students. These findings highlight the need for mental health interventions addressing both PSMU and eating disorders. Future research should use longitudinal designs to establish causal relationships.Trial registration number ChiCTR2300078008.